2016
DOI: 10.1242/jcs.184770
|View full text |Cite
|
Sign up to set email alerts
|

Danon disease – dysregulation of autophagy in a multisystem disorder with cardiomyopathy

Abstract: Danon disease is a rare, severe X-linked form of cardiomyopathy caused by deficiency of lysosome-associated membrane protein 2 (LAMP-2). Other clinical manifestations include skeletal myopathy, cognitive defects and visual problems. Although individuals with Danon disease have been clinically described since the early 1980s, the underlying molecular mechanisms involved in pathological progression remain poorly understood. LAMP-2 is known to be involved in autophagy, and a characteristic accumulation of autopha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 85 publications
(70 citation statements)
references
References 70 publications
0
67
0
3
Order By: Relevance
“…The remaining part of exon 9 encodes a transmembrane domain (24 amino acids) and a cytoplasmic tail (11 amino acids). Exon 9 undergoes alternative splicing, resulting in three different spliced isoforms, LAMP‐2a, LAMP‐2b and LAMP‐2c, which share the same luminal domain but have both different transmembrane and cytoplasmic domains (the cytoplasmic domain is the most relevant to understanding the variability of clinical manifestations) and different tissue distribution and functions in the autophagy degradation pathway (Table , Figure ).…”
Section: Pathogenetic Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining part of exon 9 encodes a transmembrane domain (24 amino acids) and a cytoplasmic tail (11 amino acids). Exon 9 undergoes alternative splicing, resulting in three different spliced isoforms, LAMP‐2a, LAMP‐2b and LAMP‐2c, which share the same luminal domain but have both different transmembrane and cytoplasmic domains (the cytoplasmic domain is the most relevant to understanding the variability of clinical manifestations) and different tissue distribution and functions in the autophagy degradation pathway (Table , Figure ).…”
Section: Pathogenetic Mechanismmentioning
confidence: 99%
“…DD was originally postulated to be caused by a glycogen storage defect of glycogen accumulation in lysosomes. However, recent studies have shown that the underlying mechanism is a block in autophagy leading to impaired fusion of autophagosome–lysosome and/or inefficient lysosome biogenesis and maturation .…”
Section: Pathogenetic Mechanismmentioning
confidence: 99%
“…86 However, continued genetic and cellular studies have suggested that it is instead a disease of deficient autophagy that leads to glycogen accumulation. 87,88 …”
Section: Intracardiac Infiltrative Cardiomyopathiesmentioning
confidence: 99%
“…88 Although most described mutations in LAMP2 affect all 3 isoforms, there are reports of mutations that only affect the LAMP2-B isoform, suggesting that deficiency of this isoform is necessary and sufficient to cause disease. 87,88 For a complete review of the molecular biology of LAMP2 in Danon, see the recent review by Rowland and colleagues 88 (2016). Generally, loss-of-function mutations are associated with an earlier age of onset compared with missense mutations.…”
Section: Intracardiac Infiltrative Cardiomyopathiesmentioning
confidence: 99%
“…As mentioned above, deficiency in LAMP‐2 protein causes lysosomal glycogen storage problems in the affected cell types (e.g., cardiomyocytes and neurons) in Danon patients. Given the function of LAMP‐2 in lysosome biogenesis and autophagy (Rowland et al, ), LAMP‐2 knockout mice displayed accumulation of autophagic vacuoles and cardiomyopathy (Saftig et al, ). iPSC technology made it possible to explore the effects of LAMP‐2 deficiency in human cells.…”
Section: Introductionmentioning
confidence: 99%